(untitled) (American Journal of Islam and Society, 2004)
Though women’s studies and Islamic studies have not often met in scholarly discourse, Gender, Politics and Islam is evidence that they should. This book is a testament to the breadth and quality of scholarship in Muslim women’s studies. All of its articles originally appeared in Signs: Journal of Women in Culture and Society, of which Therese Saliba, Carolyn Allen, and Judith A. Howard, previously served as editors and associate editors. Saliba’s competent introduction summarizes the articles and promptly debunks simplistic understandings of Muslim women and their lives, and highlights their diverse and complex engagements with religion, politics, society, and culture. Not only does this introduction speak for and to nuanced understandings of Islam and Muslims, it also links feminist struggles transnationally and explicitly positions itself against the exceptionalism of Muslim women. Although all nine chapters were previously published, this volume merits separate publication for several reasons. First, it promotes good scholarship on Muslim women. Second, it undoubtedly will reach a larger audience as a collection than as individual articles. This audience includes not only those outside academia, but also academics who might not normally read specialized women’s studies journals – many in the field of Islamic studies, traditionally defined, for example. Moreover, the book could be used effectively in teaching Islamic studies and women’s studies; indeed, some of its articles are already being used this way. Though the articles were not written for a general audience, many could easily appeal to the interested nonspecialist. Finally, these serious, scholarly essays complement each other and represent a breadth of disciplinary approaches (e.g., literary studies, sociology, history, anthropology, and political science), geographical regions (e.g., Iran, Pakistan, Palestine, Lebanon, Yemen, Bangladesh, and Canada), and issues (e.g., legal rights, religious rituals, political empowerment, reception politics, and Islamic feminism, among many others). Despite this breadth, each essay speaks extremely well to at least several others and highlights Muslim women’s strategies and practices of crafting spaces for action and engagement in politics and society. Valentine Moghadem’s “Islamic Feminism and its Discontents: Towards a Resolution of the Debate” provides an overview of Iranian women’s many contrasting positions in relation to their rights in the Islamic Republic. She also draws useful comparisons between U.S. liberal feminists and Iranian Islamic feminists, thereby providing an analysis of current trends, issues, and debates. “The Politics of Feminism in Islam,” by Anouar Majid, continues this inquiry into women crafting a feminist theory and practice that engages Islam. Like Moghadem, he sees a positive side to Iran’s Islamic feminist movement, as it resists “the effects of global capitalism and contributes to a rich egalitarian polycentric world” (p. 87) ...